Exploring the impact of workplace violence on defensive medicine and patient outcomes: an empirical analysis using regression discontinuity - Guoheng Hu; Ying Li; Haining Zhao (BMC Health Services Research)
Abstract Objective This study aims to thoroughly examine the impact of workplace violence incidents in healthcare settings on the structure of medical expenses, with a particular focus on specific changes in defensive medical, and to further investigate the resulting patient outcomes. Method This study examines a high-profile workplace violence incident in W City, H Province, China, which had widespread societal impact, treating it as an exogenous shock. Utilizing inpatient medical record data from W City, the study constructs a regression discontinuity model to systematically analyze shifts in medical behaviors related to costs and decision-making following the incident, as well as the implications of these changes on patient burden and health outcomes. Results The findings indicate that workplace violence incidents lead to significant changes in the structure of medical costs, with a notable increase in comprehensive medical service fees and a significant decrease in invasive treatment fees. Further analysis reveals that such incidents trigger pronounced defensive medicine, including extended hospital stays, increased probabilities of departmental transfers, reduced surgical levels, and higher costs and a greater proportion of traditional Chinese medicine in total expenditures. Additionally, in terms of patient outcomes, workplace violence incidents slightly alleviate patients’ out-of-pocket expenses and payment ratios. However, these incidents significantly worsen patients’ primary health indicators and overall health status at discharge. Conclusion Workplace violence against healthcare professionals significantly impact the structure of medical costs and trigger defensive medicine, characterized by a tendency toward conservative treatment approaches and reduced treatment intensity. While such incidents may partially alleviate patients’ financial burdens, they have detrimental effects on patients’ health outcomes. Therefore, to enhance healthcare quality and safeguard patient well-being, it is imperative to implement measures to mitigate workplace violence in healthcare and encourage medical institutions to prioritize scientific and rational decision-making in treatment practices.